SEMANTIC CHANGES USED BY MILLENNIAL GENERATION ON INSTAGRAM - Yashinta Farahsani; Patria Handung Jaya; Ika Puspita Rini (Universitas Bandar Lampung, 2021)
Instagram is an application that lets users take photos and videos then share them on various social media. They also can put representative comments in those photos and videos. One interesting thing about the Instagram users' comments is they always update the new vocabulary developed in cyberspace which is then applied in the real world. In Indonesia, Instagram users also do the same, therefore many new vocabularies emerge and are used, for example, tercyduk, ngakak online, salfok, baper, etc. This research aims to find out the types of those new vocabularies based on their category and meaning, and also the use of those vocabularies. The semantic approach is used in analyzing the words because this approach focuses on finding the meaning of a word or a phrase. Therefore, after knowing the meaning, it will be easier to find out the use of each word or phrase